2018
DOI: 10.3390/app8081267
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Limitations in the Identification of Acoustic Emission Signature of Damage Mechanisms in Composites Materials

Abstract: Acoustic emission is a part of structural health monitoring (SHM) and prognostic health management (PHM). This approach is mainly based on the activity rate and acoustic emission (AE) features, which are sensitive to the severity of the damage mechanism. A major issue in the use of AE technique is to associate each AE signal with a specific damage mechanism. This approach often uses classification algorithms to gather signals into classes as a function of parameters values measured on the signals. Each class i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…Most of the time, acoustic emission is collected from resonant sensors due to their good sensibility. However, waveform characterization is strongly dependent on sensor features [ 17 , 18 , 19 ]. Therefore, the effects of sensors’ types are still a challenge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the time, acoustic emission is collected from resonant sensors due to their good sensibility. However, waveform characterization is strongly dependent on sensor features [ 17 , 18 , 19 ]. Therefore, the effects of sensors’ types are still a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…It can only obtain partial information and therefore cannot get accurate information about the damage. Several studies have shown that using one type of sensor has many limitations in identifying acoustic signatures [ 17 , 18 , 19 ]. This emphasizes the interest of using multiple data sources and data fusion.…”
Section: Introductionmentioning
confidence: 99%
“…From the contemporary research on delamination in laminated composites, it can be found that most of the research efforts are dedicated to the use of higher-frequency guided waves (e.g., Lamb waves), acoustic emission/acoustic ultrasonic, and mode shape curvatures for the detection, quantification, and localization of delamination [43][44][45][46][47][48][49]. This paper proposes a deep learning framework for the assessment of delamination in piezo-bonded laminated composites using low-frequency structural vibration responses.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the shift illustrated in Figure 1b, may be a result of the propagation conditions that mask the characteristics of the source. Indeed, the propagation distance has been shown to be a crucial factor influencing the classification [14,22,23] because of the more effective attenuation of the higher frequencies as well as the "spreading" of the waveforms in the time domain. Apart from experimental AE studies, there are several numerical works on the subject of wave propagation in plates, some examples are shown in [24][25][26].…”
Section: Introductionmentioning
confidence: 99%